SISTEM USAHATANI TANAMAN DAN TERNAK SAPI DI LAHAN KERING KALIMANTAN SELATAN (STUDI KASUS DI DESA BANUA TENGAH DAN SUMBER MAKMUR, KECAMATAN TAKISUNG KABUPATEN TANAH LAUT) - Eni Siti Rohaeni (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Farming  is  done  in  general  farmers  polyculture  with  the  aim  to  increase revenues  and  avoid  crop  failure.  Farming  is  carried  out  consisting  of  several commodities both crops and livestock. Generally farming is done  is still not provide sufficient revenues Living Needs. This study aims to determine the system of crop and cattle  farming  in  upland  South  Kalimantan,  and  to  determine  whether  the  income generated from farming to meet to the needs of decent living. This research is a case study in the village of Central Banua and Sumber Makmur, Takisung district, Tanah Laut regency. This study was conducted in 2012. Research was conducted by way of a survey approach Focus Group Discussion conducted with the involvement of several community leaders /key figures to describe the profile , potential and problems in the region or village level. The analysis used is analysis of revenue, contribution revenue, and contribution to the farm income Living Needs (KHL). The results showed  that the dominant  farming  by  farmers  in  the  study  site,  namely  rice,  sweet  corn  and  cattle. Mean scale paddy cultivation to 0.62 ha, 0.68 ha of sweet corn and cattle 5.15 Animal Unit. Farming is done generating the value of R/C is more than one viable means for cultivated. The revenue contribution of rice 24.52 %, 50.83 % sweet corn and cows 24.65 % . Contribution income from rice farming, sweet corn and beef cattle on Living Needs of 50.94 %.